2007
DOI: 10.1016/j.jns.2006.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and cerebrovascular responses to lower body negative pressure in type 2 diabetic patients

Abstract: In diabetic patients, vascular disease and autonomic dysfunction might compromise cerebral autoregulation and contribute to orthostatic intolerance. The aim of our study was to determine whether impaired cerebral autoregulation contributes to orthostatic intolerance during lower body negative pressure in diabetic patients.Thirteen patients with early-stage type 2 diabetes were studied. We continuously recorded RR-interval, mean blood pressure and mean middle cerebral artery blood flow velocity at rest and duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The above mentioned variability of BP and CBFV changes upon orthostatic challenge [21,25,50,51,53,54], with no change or a decrease in one or both signals, or even diametrical changes,…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The above mentioned variability of BP and CBFV changes upon orthostatic challenge [21,25,50,51,53,54], with no change or a decrease in one or both signals, or even diametrical changes,…”
Section: Discussionmentioning
confidence: 99%
“…Marple [45] and applied in many previous studies assessing PA as a parameter of cerebral autoregulation [10,24,25,29,30,40,43,46].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may reflect the small size of studies. The development of impaired dynamic cerebral autoregulation may also relate to disease duration, although studies of similardisease duration have [4,5] and have not [7,8] reported impaired dynamic cerebral autoregulation. However, we did not find an increased likelihood of impaired dynamic cerebral autoregulation in patients with a diseasedurationgreaterthan5 years.Anothercontributormaybe disease severity, although the present study excluded insulintreated patients, and only approximately 30% of patients had evidence of macro-or microvascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…People with diabetes may be particularly susceptible to the consequences of impaired cerebral autoregulation, being at increased risk of cerebral hypoperfusion secondary to autonomic neuropathic‐related orthostatic hypotension, and cerebral atherothromboembolism as a result of accelerated atherosclerosis. However, the few previous cerebral autoregulation studies in diabetes have produced conflicting results, showing impaired dynamic cerebral autoregulation [4–6] or no difference compared with control subjects [7,8]. These differences may be a consequence of small study size and the different methodologies and indices used to assess cerebral autoregulation.…”
Section: Introductionmentioning
confidence: 99%